Surround mixing in pro tools LE - MICKIEWICZ, Witold; JELEŃ, Jakub (Archives of Acoustics, 2008)
Today’s multimedia use surround sound extensively, and most often in format 5.1. A lot of popular software packages used for sound production, including Pro Tools in LE version, do not have the ability to form mixes in this format. However, thanks to an appropriate configuration of internal audio buses and the cooperation with the multichannel input/output interface, this mode of operation is possible. Unlike other proposals, based only on send channels to individual output channels, the authors present a new configuration that uses the Pro Tools LE software. Thanks to this configuration, placing an apparent source of sound in the surround space becomes more intuitive, as it is accomplished through the use of panning sliders which determine space coordinates. Direct send channels serve exclusively to form the central and low frequency effect channel (LFE). This configuration was applied to make the final mixdown of a multichannel recording of the choir concert with the use of the Optimized Cardioid Triangle (OCT) microphone array.